Pengembangan Model Manajemen Berbasis Website Careedu untuk Penanganan Isu Psikososial Siswa SMA di Maluku Barat Daya - Ester Tiwery; Hardiansyah Masya; Nova Erlina (Attractive : Innovative Education Journal, 2026)
This research is motivated by the high prevalence of bullying and limited access to mental health services in the archipelagic region of Southwest Maluku (MBD). Schools still use conventional approaches with manual recording and unstructured reporting systems. The study aims to describe current psychosocial issue management, analyze its weaknesses, and develop a website-based management model. This research employs the R&D method with the ADDIE model. Research subjects included the principal, guidance counselors, homeroom teachers, and 151 students of State Senior High School 13 MBD. Data wascollected through interviews, observation, FGD, questionnaires, and document studies. Product validation was conducted by IT experts and educational management experts, followed by practicality and effectiveness tests. The results reveal: (1) Current psychosocial issue management in MBD remains manual, reactive, and unintegrated with high underreporting rates; (2) Main weaknesses include absence of standardized recording systems, data fragmentation, and deeply rooted reluctance to report; (3) The CareEdu website model was developed featuring case reporting, early detection, analytical dashboards, and contextual educational content. IT expert validation scored 86.65% (very valid), material expert 96.67% (very valid), practicality test 89.09% (very practical), and effectiveness increased from 54.25% to 90.04% (very effective). This research concludes that the CareEdu model is effective, practical, and valid as an innovative solution for handling adolescent psychosocial issues in archipelagic regions.